Epidemiology, clinical features, and associated factors in 78 cases of lichen planus on black skin. (20th October 2019) - Diop, Assane; Ly, Fatimata; Ndiaye, Mame Tene; Seck, Birame; El Omari, Amal; Diouf, Astou; Tajaoui, Myriam; Diadie, Saer; Ahy Diatta, Boubacar; Ndiaye, Maodo; Diallo, Moussa; Niang, Suzanne; et al.
Abstract: Background: The pathogenesis of lichen planus (LP) is mostly autoimmune, while psychological and infectious factors are recognized to trigger or aggravate the disease. An association with diabetes is reported. Our objective was to determine the epidemio‐clinical characteristics of LP and its associated factors. Methods: This multicentric, prospective study was conducted over a 6‐month period. The histopathology was only performed for atypical forms. Patients with a notion of drug intake before the rash were excluded. Anti‐hepatitis C Virus (HCV) antibodies screening was systematical in case of mucosal damage. The data were analyzed using the SPSS IBM 20 software. Results: The average age was 38 years. Women represented 84.6% ( n  = 66) of the studied population. The patients were married in 61.5%. Obesity or overweight status was noted in 41%. A marital or relational conflict was found in 25.6%. History of LP was reported in 24.4% ( n  = 19). Pruritus was found in 96.2%. The locations were as follows: skin (97.4%), mucous membranes (15.4%), and hair and nails (5.1%). Lesions were diffuse in 56.4%. The clinical forms were as follows: typical (52.6%), erythematosquamous (17%), warty (14.5%), pigmented (14.5%), and blaschkolinear (one case). Histopathology confirmed the diagnosis of LP in 91.4%. Blood sugar level was high in one case. Hepatitis B surface antigen (HBsAg) was positive in 3.03%. Anti‐HIV and anti‐HCV antibodies were negative. Conclusion: Lichen planus is a relatively rare disease in sub‐Saharan Africa and is seen more in adults. The clinical manifestations are polymorphic, but the mucosal damage is rarely isolated.